Dilated cardiomyopathy associated with celiac disease: A case report. Issue 11 (12th November 2021) - Elnour, Salma; Hashim, Maram; Ibrahim, Halah
Abstract: Background: Celiac disease, an immune‐mediated inflammation of the small intestine, occurs in genetically predisposed individuals, and is caused by sensitivity to dietary gluten and related proteins. The global prevalence is approximately 1%. Celiac disease is frequently associated with extra‐intestinal manifestations, including iron deficiency anemia, dermatologic eruptions, type 1 diabetes mellitus, thyroid disease, and connective tissue disorders, but is rarely associated with cardiomyopathy.Case presentation: Our case describes a 33‐year‐old woman, who presented with exertional dyspnea and fatigue, and was diagnosed with severe iron deficiency anemia and dilated cardiomyopathy, secondary to celiac disease. Conclusion: High clinical suspicion is needed to identify celiac disease in patients diagnosed with dilated cardiomyopathy, as an improvement in cardiac function has been reported with strict adherence to a gluten‐free diet. Abstract : Celiac disease is an autoimmune disease that is associated with different conditions. Cardiomyopathy associated with celiac disease needs high degree of clinical suspicion to make the diagnosis, as a gluten‐free diet can improve heart function.